Black Twig Borer, Xylosandrus compactus (Eichhoff) (Insecta: Coleoptera: Scolytidae) - Wayne N. Dixon; Robert E. Woodruff; John L. Foltz (EDIS, 2023)
The black twig borer, Xylosandrus compactus (Eichhoff), is one of the few ambrosia beetles that infests healthy plants. In Florida, orchids (Dendrobium spp. and Cattleya spp.), and avocado (Persea americana Mill.) have sustained notable economic losses (Dekle and Kuitert 1968, McClanahan 1951). Although ornamental shrubs and shade trees seldom die from beetle infestations, the loss of growth and aesthetics can be substantial. Elsewhere, the black twig borer is a serious pest of coffee, Coffea canephora Pierre (esp. var. robusta Ineac) (Brader 1964). This document is EENY-311, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2003. Revised: September 2005.